2017
DOI: 10.1590/1980-5373-mr-2016-0675
|View full text |Cite
|
Sign up to set email alerts
|

Emission Properties Related to Distinct Phases of Sol-Gel Dip-Coating Titanium Dioxide, and Carrier Photo-Excitation in Different Energy Ranges

Abstract: Titanium dioxide (TiO 2 ) in the form of pellets (pressed powder) and thin films are investigated, revealing the presence of distinct phases: mainly anatase and rutile. Characterization of optical, structural and electrical properties were carried out on samples submitted to different sort of thermal annealing (TA), at distinct temperatures, 500 and 1000 o C, due to their influence on the obtained phases. TA temperature along with pressure application for sample conformation, determine the bands present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The bandgap was estimated through the Tauc method, and the value of the indirect bandgap is 3.6 eV, in good agreement with published results [7,27]. Figure 2b shows the transmittance (inset) of the TiO 2 layer and its indirect bandgap estimative of 3.4 eV, also in agreement with published data [1,11]. The thickness of both films were estimated through the interference fringes present in the transmittance data [28], and the values are 380 nm for Sb:SnO 2 , and 360 nm for TiO 2 films.…”
Section: Individual Tio 2 and Sno 2 Layerssupporting
confidence: 87%
See 2 more Smart Citations
“…The bandgap was estimated through the Tauc method, and the value of the indirect bandgap is 3.6 eV, in good agreement with published results [7,27]. Figure 2b shows the transmittance (inset) of the TiO 2 layer and its indirect bandgap estimative of 3.4 eV, also in agreement with published data [1,11]. The thickness of both films were estimated through the interference fringes present in the transmittance data [28], and the values are 380 nm for Sb:SnO 2 , and 360 nm for TiO 2 films.…”
Section: Individual Tio 2 and Sno 2 Layerssupporting
confidence: 87%
“…Sol-gel fabrication of TiO 2 was carried out by hydrolysis and condensation of titanium (IV) isopropoxide using a high molar ratio of water:alkoxide (200:1), isopropanol as co-solvent, HNO 3 as catalyst, and Triton X-100 as surfactant [11,23,24]. Initially 2.6 ml of Nitric acid was added to 185 ml of deionized water and 57 ml of isopropanol solution, followed by dropwise addition of 15 ml of titanium (IV) isopropoxide alkoxide under stirring and heated at 85 °C for 4 h. The concentration of solution was performed by evaporating the solvent and dispersants at 100 °C until reach a volume of 50 ml, which was followed by the addition of the surfactant, under stirring for 30 min.…”
Section: Experimental Details 21 Thin Films Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The optical bandgaps are close to those experimentally observed for TiO 2 that displays bandgap around 3.2 and 2.9 eV for anatase and rutile phases, respectively ( Ivanova et al, 2016 ; Munir et al, 2019 ). The anatase phase has an indirect bandgap, while the rutile presents direct electronic transitions ( Ramos Jr et al, 2017 ). Abdel-Fattah et al (2019) reported the direct and indirect optical bandgaps of PVC film around 4.2–4.3 eV, which are values higher than those experimentally observed in our PVC system.…”
Section: Resultsmentioning
confidence: 99%
“…Some are complex and expensive as is the case of sputtering and electron beam deposition [24,25]. Some others are cheap and easy to work with, as is the case of spray pyrolysis, spin coating, dip coating and chemical bath deposition [26][27][28][29]. Also, new techniques or modified versions of the existing techniques are being explored, as is de case of the sol-gel ultrasonically assisted that has been used to obtain pure rutile phase powders and to obtain smaller grain sizes and larger surface areas when compared with the standard sol-gel technique [30,31].…”
Section: Introductionmentioning
confidence: 99%